Sex-specific associations of vascular risk factors with abdominal aortic aneurysm: Findings from 1.5 million women and 0.8 million men in the USA and UK - Carter, JL; Morris, DR; Sherliker, P; Clack, R; Lam, KIN; Halliday, A; Clarke, R; Lewington, S; Bulbulia, R (Wiley, 2020)
Background: Large studies are required for reliable estimates of important risk factors for abdominal aortic aneurysm (AAA). This could guide targeted AAA screening programs, particularly in subgroups like women who are currently excluded from such programs.